Acid suppression in duodenal ulcer: a meta-analysis to define optimal dosing with antisecretory drugs. Issue 9 (September 1987) - Jones, D B; Howden, C W; Burget, D W; Kerr, G D; Hunt, R H
Abstract : FVMany different dosage schedules of antisecretory drugs for the treatment of duodenal ulcer are recommended. The relationship between degree of acid suppression and therapeutic efficacy has not been precisely defined for these drugs. We have examined the association between suppression of intragastric acidity and duodenal ulcer healing rates for a number of therapeutic regimens. For the H2 receptor antagonists alone, the most significant correlation with healing rates was with suppression of intragastric acidity at night (r = 0.926; p = 0.0001). When other classes of drug: high dose antacid, omeprazole and a synthetic prostaglandin (enprostil) were included in the analysis, the closest correlation was with suppression of total 24 hour intragastric acidity (r = 0.911; p less than F0.0001). Stepwise linear regression analysis was used to investigate the relative contributions to healing of suppression of acidity during the day and night. Suppression of nocturnal acidity was found to be the single most important factor in explaining healing rates. No further benefit was obtained with daytime suppression for H2 receptor antagonists; suppression of acidity at night accounted for 86.1% of the observed variation in healing rates among different regimens of H2 receptor antagonists. When all classes of drugs were analysed, inclusion of daytime suppression produced a significant improvement in correlation over nocturnal suppression alone. Drug regimens providing potent suppression of nocturnal acidity produce the highest healing rates in controlled clinical trials. The healing rate for any dose regimen of an antisecretory drug can be predicted from a knowledge of its effect on intragastric acidity. For the H2 receptor antagonists, suppression of nocturnal acidity is the most relevant in this context. Moderate suppression of acidity achieves ulcer healing rates at four to eight weeks which are comparable with those seen with potent suppression at two to four weeks. Increasing degrees of suppression merely accelerate healing.